Form of Magic Words in The Process of Language Acquisition for Children Aged 2-4 Years - Reistanti, Agustina Putri; Fawziyyah, Safynatul; Ayuningtyas, Septian (Indonesian Journal of Early Childhood Education Studies, 2023)
This research aims to describe the early childhood language acquisition process at KB Aisyiyah 1 Balun, Cepu District, Blora Regency. This type of research is descriptive qualitative. Two research subjects were taken in each group, so there were six research subjects. The data collection method used several techniques, namely observation, listening, recording, and note-taking. The research results show that children can achieve language competence at the phonology, morphology, syntax, and semantics levels. Language acquisition results in phonology show that the phonemes /r//l/ sound faint. Phoneme decay is the melting of phonemes due to morphological processes. The /l/ phoneme decays when the/y/phoneme's sound changes to the /l/ phoneme. The results of language processing in the field of morphology are that children aged two years have just mastered the basic morphemes that are pronounced even though the pronunciation is not yet clear. Meanwhile, many sulfides (- kan ) are found in children aged four years. Early childhood language acquisition in the area of syntax identified phrase errors, children's composition of first language sentences was mixed up, and sentence structures were adequate, although sometimes grammatically, sometimes inverted. Meanwhile, language acquisition at the semantic level tends to use denotative Meaning in every utterance.